Adherence and persistence with istradefylline treatment in patients with Parkinson’s disease in the United States - Joseph, Reversa; Qian, Joyce; Cummings, Hannah; Chen, Yen-Hua; Tewari, Shubham; Soileau, Michael (Frontiers in Pharmacology, 2025)
BackgroundMedication adherence and persistence are associated with better outcomes for patients with Parkinson’s disease.ObjectivesTo evaluate 12-month adherence and persistence with istradefylline and identify factors associated with persistence among patients.MethodsA retrospective cohort study was conducted using IQVIA longitudinal prescription (LRx) and medical (Dx) claims data. Adult patients initiating istradefylline between 2019 and 2022 with ≥1 LRx and ≥1 Dx claim every 6 months over 12-month baseline and follow-up periods were included. Adherence was measured by the proportion of days covered (PDC) and medication possession ratio (MPR). Persistence was measured by the duration of prescription fills, allowing for a ≤60-day gap. Multivariate logistic regression was used to evaluate factors associated with 12-month persistence.ResultsAmong 2,045 patients, 76.0% were covered by Medicare Advantage and 23.9% were commercially insured. Over 12 months of follow-up, median adherence (both PDC and MPR) was 74.0% and median persistence was 276 days. In a subgroup analysis, median adherence and persistence were significantly greater in patients with Medicare Advantage versus commercial insurance (PDC and MPR: 82.2% vs. 49.3%; persistence: 365 days vs. 180 days; all P < 0.001). Treatment initiated at 40 mg versus 20 mg (odds ratio [OR]: 1.33 [95% confidence interval [CI]: 1.10, 1.62]) and Medicare Advantage versus commercial insurance (OR: 1.79 [95% CI: 1.42, 2.26]) were independently associated with longer persistence.ConclusionPatients initiating istradefylline at 40 mg versus 20 mg and those with Medicare Advantage versus commercial insurance were more likely to have higher adherence and longer persistence with istradefylline.